The effect of ethanol on surface of semi-interpenetrating polymer network (IPN) polymer matrix of glass-fibre reinforced composite - Santhosh Basavarajappa; Leila Perea-Lowery; Sultan Aati; Abdul Aziz Abdullah Al-Kheraif; Ravikumar Ramakrishnaiah; Jukka Pekka Matinlinna; Pekka K. Vallittu (Elsevier Ltd, 2022)
Aim of the study:The aim of this laboratory study was to evaluate the effect of ethanol treatment on the surfaceroughness (Sa), nano-mechanical properties (NMP) and surface characterization of dentalfiber reinforcedcomposite (FRC) with semi-interpenetrating polymer network (IPN).Materials and methods:A total of 240 FRC specimens with bisphenol A-glycidyl methacrylate - triethyleneglycoldimethacrylate–Poly (methylmetahcrylate) (bis-GMA-TEGDMA-PMMA) IPN matrix system were light cured for40 s and divided into 2 groups (L and LH). The group LH was further post-cured by heat at 95 °C for 25 min. Thespecimens were exposed to 99.9%, 70% and 40% for 15, 30, 60 and 120 s respectively. The treated specimenswere evaluated for Sausing non-contact profilometer. NMP were determined using nanoindentation techniqueand chemical characterization was assessed by Fourier Transform-Infrared (FTIR) spectroscopic analyses.Scanning electron microscopic (SEM) images were made to evaluate the surface topographical changes.Results:Both the L and LH group showed changes in the Saand NMP after being treated by different con-centrations of ethanol and at different time interval. The highest Sawas observed with L-group (0.733μm)treated with 99.9% ethanol for 120 s. Specimens in LH-group treated with 99.9% ethanol for 120 s (1.91 GPa)demonstrated increased nano-hardness, and group treated with 40% ethanol for 120 s demonstrated increasedYoung's modulus of elasticity (22.90 GPa). FTIR analyses revealed changes in the intensity and bandwidth inboth the L and LH groups.Conclusion:The present study demonstrated that both light-cured and heat post-cured FRC were prone forethanol induced alteration in the surface roughness (Sa), nano-mechanical properties (NMP) and chemicalcharacterization. The interphase between the glassfibers and the organic matrix was affected by ethanol. Thechanges were considerably less in magnitude in the heat post-cured FRC specimens.